(untitled) (e-Journal of Linguistics, 2025)
This writing is intended to investigate the form, formation, and meaning of lexicons mbaru gendang, a traditional house possessed by Manggaraian ethnic group in the western part of Flores island-NTT-Indonesia. The study was done under the qualitative method. The data were collected by observing the construction of mbaru gendang and the processes of how the house is built. The result reports that the form of lexicons mbaru gendang are two namely simple and complex lexicons. They are formed through the zero derivation and combination processes. Those two processes influence the lexicons category which then included as nouns and verbs. Furthermore, the meaning of lexicons mbaru gendang consists of synonyms, antonyms, homonyms, and hyponyms.